Does Low-Magnitude High-Frequency Vibration (LMHFV) Worth for Clinical Trial on Dental Implant? A Systematic Review and Meta-Analysis on Animal Studies - Ye, Xinjian; Gu, Ying; Bai, Yijing; Xia, Siqi; Zhang, Yujia; Lou, Yuwei; Zhu, Yuchi; Dai, Yuwei; Tsoi, James Kit-Hon; Wang, Shuhua (Frontiers in Bioengineering and Biotechnology, 2021)
Being as a non-pharmacological medical intervention, low-magnitude high-frequency vibration (LMHFV) has shown a positive effect on bone induction and remodeling for various muscle diseases in animal studies, among which dental implants osteointegration were reported to be improved as well. However, whether LMHFV can be clinically used in dental implant is still unknown. In this study, efficacy, parameters and side effects of LMHFV were analyzed via data before 15th July 2020, collecting from MEDLINE/PubMed, Embase, Ovid and Cochrane Library databases. In the screened 1742 abstracts and 45 articles, 15 animal studies involving 972 implants were included. SYRCLE's tool was performed to assess the possible risk of bias for each study. The GRADE approach was applied to evaluate the quality of evidence. Random effects meta-analysis detected statistically significant in total BIC (P<0.0001) and BV/TV (P=0.001) upon loading LMHFV on implants. To conclude, LMHFV played an active role on BIC and BV/TV data according to the GRADE analysis results (medium and low quality of evidence). This might illustrate LMHFV to be a worthy way in improving osseointegration clinically, especially for osteoporosis.